Prediction of the Kinematic Viscosity of Libyan Crude Oil as a Function of its Specific Gravity as One Input Data - Ali Abdullah,; Salah Idris,; Wafa Abdullah, (AlQalam Journal of Medical and Applied Sciences, 2023)
The prediction of the kinematic viscosity of some Libyan crude oils based on its specific gravity as one input parameter has been investigated. The correlation was developed in order to improve on the accuracy of existing correlations and to assist oil kinematic viscosity where the knowledge of viscosity of uncharacterized crude oils is required. The data used to build the correlation consist of measurements from 4 crude oils from various locations around Libya, the range from 0.81 to 0.84 g/cm3, resulting in kinematic viscosity values ranging from 5 – 11 mm2/s. The correlation can be used as far as the specific gravities’ values are available. When a single specific gravity measurement is available at 15oC, it can predict the viscosity at 40 oC with an average absolute deviation (AAD) of 6.58%, which is an improvement in accuracy compared to previously published correlations (Puttagunta) with the kinematic viscosity at 37.8 as one input for kinematic viscosity prediction was 7.17%. Finally, when a t-test which is an inferential statistic used to determine if there is a significant difference between the means of experimental and theoretical data of kinematic viscosity, the difference was considered to be not statistically significant. It is worth noting that the required input for this equation is only the specific gravity. تم التحقيق في معرفة قيمة اللزوجة الحركية لبعض خامات النفط الليبية باستخدام الكثافة النوعية كمعامل وحيد يتم ادخاله في علاقة رياضية للتنبؤ بقيمتها. حيث تم تطوير العلاقة بهدف تحسين دقة العلاقات السابقة المستخدمة لهذا الغرض والمساهمة في تقدير اللزوجة الحركية عند غياب بيانات دقيقة عن خامات النفط. استُخدمت بيانات مأخوذة من قياسات أربع خامات نفطية من مواقع مختلفة في ليبيا وهي خام ماجد والحمادة والسرير والبيضاء البيضاء ، حيث تراوحت قيم الجاذبية النوعية بين 0.8140 و0.8370 جم/سم³، وأسفرت عن لزوجة حركية تتراوح بين 5 و11 مم²/ثانية على التوالي. حيث نتج من معادلة الخط المستقيم علاقة يمكن استنتاج منها معادلة رياضية تكون ذات قيمة عند توفر الكثافة النوعية للنفط المراد تعيين لزوجته الحركية، فيمكن للعلاقة التنبؤ بلزوجة النفط عند درجة حرارة 40 مئوية بمتوسط انحراف مطلق (AAD) يبلغ 6.58%، مما يمثل تحسنًا في الدقة مقارنة بالعلاقات المنشورة سابقًا مثل علاقة (Puttagunta) التي مقدار الدقة لها 7.17% . أظهرت نتائج اختبار t في هذه الدراسة أن قيمة P ثنائية الطرف تساوي (0.9446)، وأن متوسط الفرق بين النتائج التجريبية والنتائج النظرية يساوي (-0.0540)، معدل ثقة بنسبة (95%) لهذا الفرق تتراوح بين (-1.6181 إلى 1.5101). ووفقًا للمعايير التقليدية، يعتبر هذا الفرق غير معنوي من الناحية الإحصائية مما يؤكد صلاحية هذه العلاقة لاستخدامها لمعرفة قيمة اللزوجة الحركية لخام النفط عند معرفة الكثافة النوعية فقط له